Economic, social, and professional challenges of madrasa graduates in Pakistan: Pathways for transformative reform - Samreen Abdullah; Mehboob-Ur-Rehman Mehboob-Ur-Rehman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
Madrasa education constitutes a significant component of Pakistan’s educational landscape; however, its graduates often face persistent economic, social, and professional marginalization due to limited alignment between traditional curricula and contemporary societal demands. Despite their strong grounding in Islamic scholarship, many graduates struggle to access diverse employment opportunities and social mobility. This study aims to examine the economic, social, and professional challenges faced by madrasa graduates in Pakistan and to explore reform-oriented strategies that enhance their social inclusion and employability without compromising religious identity. Employing a mixed-methods design, data were collected through questionnaires administered to approximately 100 madrasa graduates affiliated with major religious boards across Pakistan, complemented by semi-structured interviews with graduates, educators, and madrasa administrators. Descriptive, analytical, and comparative approaches were used to identify recurring patterns and structural constraints. The findings reveal that curriculum rigidity, resistance from senior religious authorities, lack of vocational and technical training, and limited pedagogical innovation significantly hinder graduates’ integration into mainstream society and employment sectors. However, the study also identifies strong support for gradual curriculum reform, vocational skill integration, and targeted teacher professional development. The study concludes that transformative yet context-sensitive madrasa reforms, particularly the integration of skill-based education and modern pedagogical training, are essential for empowering graduates, reducing social stigma, and strengthening madrasas’ contribution to national development. These findings offer a replicable framework for madrasa reform in comparable Muslim-majority contexts.